Penerapan Probing Prompting Learning Media Aplikasi Geogebra untuk Meningkatkan Hasil Belajar Pada Persamaan Garis Lurus - Yullah, Sofi; Susilaningtyas, Tri (FKIP Universitas Islam Jember, 2020)
Research on efforts to Increase Learning Outcomes of the Subject straight line equation with the model Probing prompting learning with media aplication geogebra for Grade VIII Students of MTs AL Majidi. Based on the results of the study the results obtained for student learning activities in the first cycle of the first meeting that is 72.2%, the second meeting was 83.3%. After making improvements in the first cycle, student learning activities have increased. In cycle II the third meeting is 81.1%, and the fourth meeting was 88.9%. As for the learning outcomes of students in the first cycle showed mastery learning that is 38.9%. After making improvements in the first cycle, student learning outcomes have increased. In the second cycle which is 81.1%. This proves that there is an increase in the use of Simulation Learning methods with the Hollywood Squares Review model on student learning outcomes.